Impact of training and equipment at the Battle of Attu, Aleutian Campaign -- historical study and current perspective. - Walters, Joshua D. (Fort Leavenworth, KS : US Army Command and General Staff College, 2015)
In the Aleutian Campaign of 1942-1943, the United States of America fought the only land battle against an invading nation on American territory during the past 100 years at the Battle of Attu. The 7th Infantry Division based out of Fort Ord, California was tasked by the War Department for the main offensive element. Initial battle plans called for a three-day operation to retake the island; unfortunately for the soldiers, the battle lasted twenty-two days. During the prolonged battle, the cold injury and wounded-in-action rates were nearly identical. This study explores the impact of inadequate training and ineffective equipment on the 7th ID soldiers whose previous focus on North Africa shifted to the North Pacific with less than three months for preparation. This study will also discuss current relevance of the lessons learned regarding the United States Arctic Strategy.